A Quality Assurance Audit of an Orthoptic-Led Virtual Neuro-Ophthalmology Clinic. Issue 1 (10th March 2023) - Smith, Joe; Hirst, Nicola; Yagan, Ali
Introduction: Neuro-ophthalmology is experiencing increasing demand. There is a lack of literature relating to how we deal with the capacity and demand issues, and the use of virtual clinics. Virtual clinics are well-recognised in other subspecialties to help deal with capacity and demand issues, with reports of non-medical-led clinics, and are supported by the National Health Services Long Term Plan and People Plan. We present a quality assurance audit of our orthoptic-led neuro-ophthalmology virtual clinic. Methods: The virtual clinic was developed in October 2014 to help deal with capacity and demand issues, however, only since 2019 have orthoptists been trained to virtually review. This paper provides a summary of a quality assurance audit that was completed to determine concurrence between orthoptic and consultant virtual reviews. Results: From January to August 2021, all patients attending the virtual clinic were reviewed by a trained orthoptist and then audited for concordance by a consultant neuro-ophthalmologist; 163 patients were identified. There was 100% agreement between orthoptic reviewers and consultants regarding visual function status and optical coherence tomography interpretation. Of the patients reviewed, 100% of patients were satisfied and 96% of patients would be happy to be seen in the virtual clinic again. Conclusions: Current demands on the neuro-ophthalmology speciality mean that we need to explore new ways of working. Our outcomes demonstrate a high level of agreement between orthoptists and ophthalmologists, and excellent patient satisfaction results. We hope this highlights where orthoptists can play an invaluable role in the care of neuro-ophthalmic patients and help deal with capacity and demand issues.